Pengaruh Pembelajaran Demonstrasi Terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) Kelas IV di Sekolah Dasar - Imas Masitoh; Aas Shofyanis; Ramdhan Witarsa (EDUCARE, 2015)
This research is motivated by the low value of learning outcomes in Natural Sciences subjects. This is because educator learning still uses conventional methods. This study includes demonstration methods in Natural Sciences subjects in the material changes in the environment and learning outcomes of students after attending learning on the subject of Natural Sciences by using the demonstration method. This study aims to determine the effect of demonstration learning on learning outcomes of fourth grade students of SDN Banjaran 9. The research method used is a quasi-experimental method. Analysis of differences using the t test analysis with the help of SPSS 16.0 for window, this analysis was used to determine the differences in the influence of the use of the demonstration method on the learning outcomes of control class students and the experimental class. Based on the results of data processing obtained significant differences in learning outcomes in Natural Sciences subjects in the experimental class and control class after getting treatment using the demonstration method. Based on the results of the above research it can be concluded that the use of demonstration methods can improve the learning outcomes of students in Natural Sciences subjects about material changes in the environment